Geophysical Characterisation of Native Clay Deposits in Some Parts of Niger State, Nigeria - Matthew Tersoo Tsepav; Azeh Yakubu; Kumar Niranjan; Mohammed Aliyu-Paiko; Mohammed S. S. Dastsugwai; Alfred Gimba; Abduljelili Uthman (Universitas Sebelas Maret, 2022)
Clay minerals are among the world’s most important and useful industrial minerals. Conductance, transmissivity and corrosity are some physical parameters for determining quality clay. Four (4) clay deposit sites in Kaffin-Koro, Dutse, Dogon-Ruwa and Kushikoko were investigated to evaluate corrosivity, the longitudinal conductance and transmissivity to determine the clay quality. Electrical resistivity method employing Schlumberger electrode array was used to determine the thicknesses and depths of the subsurface strata while Interpex 1xD software was used to interpret the data. Three (3) to four (4) layer earth models were delineated. Kaffin-Koro and Dutse showed three layer models while Dogon-Ruwa and Kushikoko revealed four layers. Moderate clay content was found in Kaffin-Koro in the second layer with longitudinal conductance value of 0.4780 siemens and thickness 0.770m at depth of 1.17m Dogon-Ruwa also had moderate clay content in the third layer with conductance value of 0.237 siemens, depth of 2.43m and thickness 1.76m. Kushikoko had low clay deposit in the second layer with conductance 0.1810 siemens and thickness 2.73 m at 4.37 m while the clay deposit in Dutse appeared to be generally poor as the longitudinal conductance values of the top two layers were less than 0.1 siemens.